System-Level Improvements in Work Environments Lead to Lower Nurse Burnout and Higher Patient Satisfaction. Issue 1 (January 2021) - Brooks Carthon, J. Margo; Hatfield, Linda; Brom, Heather; Houton, Mary; Kelly-Hellyer, Erin; Schlak, Amelia; Aiken, Linda H.
Abstract : Background: Burnout among nurses is associated with lower patient satisfaction, yet few system-level solutions have been identified to improve outcomes. Purpose: The purpose of this study was to examine the relationship between nurse burnout and patient satisfaction and determine whether work environments are associated with these outcomes. Methods: This study was a cross-sectional analysis of 463 hospitals in 4 states. Burnout was defined using the Maslach Burnout Inventory. Patient satisfaction was obtained from the Hospital Consumer Assessment of Healthcare Providers and Systems survey. Results: Fifty percent of hospitals where burnout is high have poor work environments, which is strongly related to lower patient satisfaction. Conclusions: High levels of nurse burnout are associated with lower patient satisfaction. Our findings demonstrate that hospitals can improve outcomes through investments in work environments. Abstract : Supplemental Digital Content is Available in the Text.